Representações sociais de crianças e adolescentes sobre violência contra a pessoa idosa - Alves, Karoline de Lima (2021)
INTRODUCTION: due to its magnitude, violence against the elderly represents a challenge for society as a whole and for different areas of the health sector. OBJECTIVE: to analyze the social representations of violence against elderly people constructed by children and adolescents in the school context. METHODOLOGICAL COURSE: this is exploratory research, with a mixed approach, based on the Theory of Social Representations. It was carried out in the city of João Pessoa / PB with students from the municipal education network, with two age groups: 100 children, aged between 08 - 11 years, of both sexes; 100 teenagers, from 12 - 18 years old, of both sexes. The project was approved by Protocol No. 2.739.173 and CAAE: 38177814.3.0000.5188. Thematic design was used. RESULTS: the children's data formed: Class 1: Descriptions about the aggressors; Class 2: Situations of violence and their determinants; Class 3: Types of violence and according to the percentage of each class. The similarity analysis presented the central element formed by the elderly that is directly associated with the types of violence and the sadness element. Adolescents' data formed: class 2 - Vulnerability situations: woman and elderly; class 1 - Consequences of Violence and Violation of Rights; and class 3 - Scenarios, Violence, Authors and Victim. The similarity analysis evidenced the co-occurrences: elderly, sadness; men; hit; cry and gun. Negative images were predominant, demonstrating a field of representations with quite negative dimensions as opposed to positive ones. The most central element was the word elderly, presenting links with other nuclei, such as choro, man; hit and weapon. It appears that both children and adolescents represent violence against the elderly from negative contents and these go beyond the family dimension and start to be shared in school life, aiming at a common life situation for all, that is, incorporated into their daily. FINAL CONSIDERATIONS: the results show that the representations of children and adolescents are anchored in social aspects such as the use of firearms, aggression, male aggressors, highlighting the situations and types of violence and their determinants. Positive and negative attitudes were observed, contemplating different meanings, so that the participants anchored their representations in the signifiers: man; geezer; sadness; cane, among others, such as: beating; to cry; autumn; sir; anger and weapon. The image of the elderly woman as a victim prevailed among others in which the elderly woman suffered some situation of violence. Men are also highlighted as the aggressors, the figure of the thief, the weapons and situations of urban and family violence. Therefore, the main factors that contribute to the occurrence of violence against the elderly may be related to the lack of preparation of the elderly caregiver in the family context, especially with the difficulties inherent to aging, associated with certain situations such as degenerative diseases. and other difficulties that affect the elderly, due to the impoverishment of the population that has forced an unhealthy coexistence.